Paluts / Nur Ammar Ashraf Mustafa - Mustafa, Nur Ammar Ashraf (2021)
The existed business is all about online selling of food which is dries bananas. The report includes all of the information and details on marketing strategy elements. The online sales of Dries bananas named Paluts Banana Salai is the focus of this portfolio of social media. Crispy Smoked Bananas are bananas with crispy food smoked on the outside. The smoked person is tasty as a sweet banana that melts in the mouth. It tastes crispy outside and very satisfying when bitten and chewy inside. The Salai Banana has a Halal certificate, it is originally from Bandung, Indonesia. There are also elements to promote and market the company so that the company can reach the public broadly. Some of the elements that significant for the social media portfolio are the profile of the business, hard selling and soft selling of the products. Nevertheless, the implementation of the business plan of the marketing strategy would be all the details in the report. The objective is always to provide all the customers with high-quality fresh products. Hence, enable stakeholders to work together and foster a conducive business environment.